Viabilização técnico-econômica da calibração de bomba de infusão volumétrica peristáltica linear utilizando um analisador de vazão - Oliveira, Ingrid Wutke (2019)
This study deals with to perform the technical-economic evaluation of a flow analyzer use implementation for calibration and periodic verification of linear peristaltic volumetric infusion pumps at Hospital de Clínicas de Uberlândia (HCU). For this purpose, 10 infusion pumps from the same manufacturer were analyzed at three different flow rates. The tests were carried out following some recommendations of the NBR IEC 60.601-2-24 standard, as well as the manufacturer's manual. Several metrological parameters (systematic error, repeatability, measurement uncertainty and maximum error) were estimated for all equipment evaluated. The measurement uncertainty associated with the flow values was evaluated according to the recommendations of the Guide to the Expression of Uncertainty of Measurement. The technical viability of the flow analyzer use for calibration and periodic verification of linear peristaltic volumetric infusion pumps was demonstrated. Eight infusion pumps presented negative systematic error values, indicating a tendency to provide values lower than the reference one. The pumps presented better metrological performance for higher flow values, exhibiting lower values of repeatability and expanded uncertainty. Only two infusion pumps (5 and 7) had systematic error values lower than that stipulated by the manufacturer. On the other hand, for maximum error, only five infusion pumps met the specifications. The estimated costs showed that the flow analyzer use for calibration and periodic verification of linear peristaltic volumetric infusion pumps is viable,as in about seven years, the hospital will have compensated the outsourced company for all the investment made with the donation of the pumps and the calibration.When the proposed regime was compared with the lendind regime,the hospital would have an estimated loss of approximately R$ 1 226 160,00 in 10 years.